Cancer my Master (II) - Juan Vera Martínez (Universidad de Alicante, 2016)
In this narrative the author, nurse by profession, describes in a precise and intense way the experiences that caused a huge and significant impact on your life: the diagnosis of a lung cancer. Also recounts so emotional experiences that were developed in the course of his process fraught with uncertainties treatment and, above all, emotional support, friends and family who both helped him to overcome this new phase of life in which, as he points out, both are learning thanks to his teacher: cancer.